2021
DOI: 10.1186/s40662-021-00248-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal brimonidine inhibits form-deprivation myopia in guinea pigs

Abstract: Background The use of ocular hypotensive drugs has been reported to attenuate myopia progression. This study explores whether brimonidine can slow myopia progression in the guinea pig form-deprivation (FD) model. Methods Three-week-old pigmented male guinea pigs (Cavia porcellus) underwent monocular FD and were treated with 3 different methods of brimonidine administration (eye drops, subconjunctival or intravitreal injections). Four different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Therefore, A-scan is more suitable for the measurement of AL in small animals. In fact, in most studies of small rodent myopia models, AL was measured by A-scan Yang et al, 2021;Yu et al, 2021). This is the reason why two kinds of A-scan were selected to measure the AL of rats in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, A-scan is more suitable for the measurement of AL in small animals. In fact, in most studies of small rodent myopia models, AL was measured by A-scan Yang et al, 2021;Yu et al, 2021). This is the reason why two kinds of A-scan were selected to measure the AL of rats in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Carr et al found that brimonidine at 20nmol/20 µ L (approximately 0.442ug/ µ L) and 200nmol/20 µ L (approximately 4.422ug/ µ L) of injected intravitreally was effective in slowing the progression of form-deprivation myopia in chicks [ 5 ]. Our groups previously reported similar results, in that that intravitreal injection of 4 µ g/ µ L brimonidine was effective in slowing the progression of form-deprivation myopia in guinea pigs [ 8 ]. The results of the present experiment, specifically that 4ug/ µ L intravitreally is effective, are generally consistent with the results of these two studies.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the above findings, our laboratory discovered that intravitreal injection at 4 µg/µL was effective in slowing the progression of form-deprivation myopia in guinea pigs [ 8 ], while the same concentration of brimonidine administered through eye drops and subconjunctival injections proved ineffective. This finding encourages further investigation, as different drug delivery methods affect therapeutic efficacy by influencing drug utilisation.…”
Section: Introductionmentioning
confidence: 99%
“… 28 In addition, both brimonidine eye drops and intravitreal injections were reported to be effective in inhibiting progressing myopia, mainly through slowing AL elongation. 29 , 30 …”
Section: Evidence In Animal Experimentsmentioning
confidence: 99%